Seasonal Fluctuations and the Demand for Money - Faig, Miquel (Quarterly Journal of Economics, 1989)
The reaction of money holders to the systematic seasonal changes in the level of transactions represents an interesting "experiment" for learning about the money demand function. An analysis of the seasonal fluctuations of the real quantity of money and several measures of transactions in the United States, Germany, the United Kingdom, and Canada reveals the following. First, Consumption Expenditures in Semidurables, Nondurables, and Services appears to be a good proxy for transactions in a money demand function, and superior to Gross Domestic Product or Consumption Expenditures. Second, the transactions elasticity of the demand for money is substantially lower than one.